Did he incite them or not: a critical discourse analysis of U.S. president Trump’s speech before the 2021 attack on the Capitol (Philology, 2024)
The objective of the paper is to analyze the speech Trump delivered ahead of the Jan 6, 2021, U.S. Capitol riot and to establish if it could be argued that the speech may have manipulated people into marching down Pennsylvania Avenue toward the Capitol and to have incited violence. The adopted analytical approach is Critical Discourse Analysis (CDA), and more precisely, van Dijk’s critical approach to textual macrostructures, which combines two key aspects: micro- and macro-level analyses. Van Dijk’s approach allows one to pose questions related to lexical and syntactic elements which emerge as salient in Trump’s speech. I examine 20 segments extracted from the President Donald Trump’s speech. The analysis demonstrates how his words play a major role in steering people into particular beliefs and in inciting violence.
Keywords: Donald Trump; critical discourse analysis (CDA); manipulation; political speech; Capitol riot; macrostructure